2015
DOI: 10.1093/femsyr/fov054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the ATP citrate lyase from carotenogenic yeastPhaffia rhodozyma

Abstract: ATP citrate lyase (ACL), is a key cytosolic source of acetyl-CoA for fatty acid and sterol biosynthesis and appear to be involved in carotenoid biosynthesis in yeasts. Three homologous DNA sequences encoding ACLs in Phaffia rhodozyma were isolated i.e two genes and one cDNA. The two genes were multi-intronic, with 3450-bp-coding sequences and both genes, as the cDNA, encoded identical 120.1-kDa polypeptides. Full-length amino acid sequences of these ACLs showed the two multidomains, PLN02235 and PLN02522, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…ACL is present in all eukaryotes except non-oleaginous yeasts. In animals and oleaginous basidiomycete yeasts, ACL is encoded by a single gene [26,27]; in plants and some filamentous fungi, ACL usually consists of two subunits (ACL1 and ACL2) with homology to the N-and C-terminals of the animal ATPcitrate lyase polypeptide [28]. Fatty acid content was increased in Y. lipolytica by overexpression of ACL1 and ACL2 on a non-lipogenic medium in an obese strain [29] or overexpression of ACL from Mus musculus [30].…”
Section: Introductionmentioning
confidence: 99%
“…ACL is present in all eukaryotes except non-oleaginous yeasts. In animals and oleaginous basidiomycete yeasts, ACL is encoded by a single gene [26,27]; in plants and some filamentous fungi, ACL usually consists of two subunits (ACL1 and ACL2) with homology to the N-and C-terminals of the animal ATPcitrate lyase polypeptide [28]. Fatty acid content was increased in Y. lipolytica by overexpression of ACL1 and ACL2 on a non-lipogenic medium in an obese strain [29] or overexpression of ACL from Mus musculus [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen depletion may cause the reduction of ACL activity, thereby repressing AX production [25]. As hypothesized by Chávez-Cabrera et al, there may be a second isoform of ACL that affects the balance between lipid and carotenoid synthesis and drives the metabolism pathway toward lipid over carotenoid production upon nitrogen deficiency, thereby reducing AX production [25,26]. In addition, the C/N ratio can cause differences in the proteomics profile.…”
Section: Astaxanthin Production With Meat and Bone Meal Hydrolysates ...mentioning
confidence: 96%
“…Some studies have shown that low-temperature expression of recombinant proteins from diverse origins (prokaryotes to higher eukaryotes), in P. pastoris, can increase the yield, activity, stability, secretion, and solubility [168][169][170][171][172][173][174]. For example, heterologous expression of Vitreoscilla hemoglobin (VHb) improves cell growth and recombinant protein production in various hosts, including P. pastoris.…”
Section: Cold-responsive For Protein Expression In Yeastsmentioning
confidence: 99%
“…However, the active form of the enzyme expressed was only detected when the recombinant yeast was grown at 25 °C and 300 rpm. The authors suggested that the production of the active recombinant enzyme may demand post-translational modifications such as phosphorylation and/or a suitable folding [168,177]. Some other studies have reported successful expression at low temperatures in S. cerevisiae, S. pombe, Kluyveromyces marxianus, and Y. lipolytica [178][179][180][181][182].…”
Section: Cold-responsive For Protein Expression In Yeastsmentioning
confidence: 99%